Family Ownership, Related-Party Transactions and Earnings Quality - Sa’adiah Munir; Norman Mohd Saleh; Romlah Jaffar; Puan Yatim (Asian Academy of Management Journal of Accounting and Finance, 2013)
This study empirically examines the effects of related-party transactions—which are typically associated with controlling shareholder expropriation activities—on the earnings quality of family firms in Malaysia. Furthermore, this study posits that at a low level of family ownership, the positive effects of familial value are likely to outweigh the negative effects of related-party transactions. However, in the presence of a high level of family ownership, the negative effects of related-party transactions are likely to be more substantial and reduce the benefits of familial value. Using hand-collected data from 2004 on related-party transactions and family ownership from a sample of 236 publically listed Malaysian firms, the results show that there is a non-linear relationship between family ownership and earnings quality after accounting for related-party transactions. This finding suggests that certain firms are likely to report high earnings quality if they have small levels of family ownership despite low levels of investor protection in Malaysia. However, when a family has a significant ownership stake in a firm, expropriation activities appear to negatively affect the earnings quality of the firm. This paper contributes to the literature by providing systematic evidence about the effects of related-party transactions on earnings quality of Malaysian firms.